Karakteristik Sari Buah Mangga Dengan Penambahan Konsentrasi Lemon Cina (Citrus microcarpa) - Breemer, Rachel (Politeknik Negeri Ketapang, 2024)
Mango is one of the perishable agricultural products, so good handling is needed. One of the treatments that can be done is processed into fruit juice beverage products, where citric acid is needed in making fruit juice. One fruit that has a high acid content is lemon cina. So in this study used lemon cina as a substitute for citric acid. The purpose of this study was to determine the right concentration in making mango juice. The design used in this study was a Complete Randomized Design with one factor, namely the concentration of Chinese lemon consisting of 3 treatment levels, namely 0.5% concentration; 1% and 1.5% and repeated 3 times. The parameters observed in this study are chemical parameters namely vitamin C, total dissolved solids and pH. In addition, a test of the level of liking for color, aroma, taste and overalls was also carried out. The results showed that the treatment of adding Chinese lemon concentration of 1.5% was the best treatment with vitamin C of 64.33; dissolved solids of 16.3 and pH of 3.1. In the hedonic test and hedonic quality, the likes (3.4) and yellow (3.1) colors, like aromas (3) and Chinese lemon flavors (3), likes (3.4) and Chinese lemon flavors (3), and overall likes (3.2).